The long-term prospects for world development: The main results of the INTERFUTURES project - Wolfgang Michalski (Intereconomics, 1979)
The increasing interdependence of the world economy requires the development of new approaches to policy-making. Nineteen OECD member countries and the Commission of the European Communities therefore decided to take part in a three-year (1976–1978) research project on the long-term prospects for world economic development and in the attempt to work out a general framework for the economic and social policies in the industrialised countries. Which are the conclusions and results of this research project, which has come to be known as INTERFUTURES?
Keywords: 330; OECD